2020
DOI: 10.1002/pssr.201900641
|View full text |Cite|
|
Sign up to set email alerts
|

Superionic State in Alumina Produced by Nonthermal Melting

Abstract: Density functional–based molecular dynamics reveals a transient superionic state in Al2O3 produced by nonthermal phase transition under extreme electronic excitation. At electronic temperatures above Te ≈ 2.75 eV, the oxygen sublattice exhibits fluid behavior, whereas the aluminum sublattice is in a solid state. This state exists up to Te ≈ 3.25 eV, where Al2O3 turns metallic–superionic; at Te ≈ 3.75 eV, the aluminum sublattice disorders. Quenching the superionic state under pressure >400 GPa freezes it into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
4
16
1
Order By: Relevance
“…(see our previous work [25]), mixed-bonding crystals, the band gap collapses at doses high above their damage thresholds. Finally, in ionic NaCl, the band gap slightly shrinks but does not collapse at doses up to 7.2 eV/atom.…”
Section: Naclmentioning
confidence: 79%
“…(see our previous work [25]), mixed-bonding crystals, the band gap collapses at doses high above their damage thresholds. Finally, in ionic NaCl, the band gap slightly shrinks but does not collapse at doses up to 7.2 eV/atom.…”
Section: Naclmentioning
confidence: 79%
“…This limit usually serves as a disordering structural criterion and the time evolution of the average atomic displacements is needed to unambiguously asses melting [19,20]. Bismuth Peierls-distorted crystal lattice [21,22] and mixed ionic-covalent bonded solids [23,24] are other types of crystalline solids concerned by non-thermal lattice softening.…”
Section: Introductionmentioning
confidence: 99%
“…Since the original work by Recoules et al 13 , it is generally accepted in the laser-mater interaction community that metals do not melt nonthermally. Indeed, it was shown that bulk metals typically exhibit hardening of phonon modes under intense electronic excitation, in contrast to covalently bonded materials 12 14 , materials with mixed ionic-covalent bonds 15 , 16 , or with Peierls distortions 17 . Absence of nonthermal melting in metals was confirmed in numerous subsequent ab-initio simulations for various metals, see e.g.…”
Section: Introductionmentioning
confidence: 99%